Penerapan Pemberian Aloe Vera Oil dalam Upaya Mengurangi Stretch Marks pada Ibu Hamil - Norlita, Wiwik; Isnaniar; Rahmi Amini; Suci Hidayani (As-Shiha: Jurnal Kesehatan, 2025)
Stretch marks (striae gravidarum) are a common issue experienced by pregnant women, particularly during the second and third trimesters, which can cause physical discomfort and psychological impact. Objective: This studi aimed to determine the effectiveness of aloe vera oil in reducing the number and severity of stretch marks in pregnant women. Methods: This research used a descriptive observational case studi method with a continuity of care approach conducted at the Independent Midwife Practice (TPMB) Bd. Dince Safrina, SST, M.KM, in Pekanbaru during 09 April–02 May 2025. The subjects consisted of two third-trimester pregnant women with stretch marks in the abdominal area. Theintervention involved applying aloe vera oil twice daily for 10 days, with monitoring conducted over three visits. Results: The results showed a reduction in the number of stretch marks from moderate to mild category in both respondents. Conclusion: These findings suggest that regular application of aloe vera oil can help reduce stretch marks in pregnant women. This studi recommends the use of aloe vera oil as a safe and effective non-pharmacological skincare alternative to enhance comfort and confidence during pregnancy